Authentic Expertise: Andrej Babiš and the Technocratic Populist Performance During the COVID-19 Crisis - Hartikainen, Ilana (Frontiers in Political Science, 2021)
This article studies how a technocratic populist can visually perform the authenticity and connection to ‘the low’ that is key to a populist performance while also maintaining the performance of expertise that is central to technocratic populist success. It relies on the case study of Czech prime minister Andrej Babiš and uses Facebook data from his profile in March and September-October 2020, the two peak moments of the crisis in the first and second waves of the COVID-19 pandemic. After offering a timeline of the Czech COVID-19 epidemic in 2020, it applies a dramaturgical analysis to four representative photos from Babiš’ Facebook page. It finds that Babiš was able to simultaneously articulate both expertise and authenticity, thereby both creating a connection to ‘the people’ while also articulating himself as an expert capable of handling the pandemic. He articulated expertise through a technocratic bodily performance, presenting himself as a cosmopolitan leader with international symbols of power like neutral-colored suits and elegant surroundings. At the same time, he also articulated himself as an authentic politician by showing his Facebook followers backstage imagery like a disorganized table and by showing himself as a busy man and an exceptionally hard worker. By illuminating the visual performance of technocratic populism, it offers insight into how technocratic populists constitute the expertise that their success rests on and that can also pose a threat to democratic societies, especially in a time of crisis.